2013
DOI: 10.1002/elan.201200552
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry of Native and Denatured Anticancer Antibody Rituximab at a Glassy Carbon Electrode

Abstract: Rituximab (RTX) is a human/murine chimeric monoclonal antibody (mAb) that specifically targets the transmembrane protein CD20 of B-cells. The oxidation mechanism of native and denatured RTX was investigated on glassy carbon electrode. The denaturing agent sodium dodecyl sulfate and the redutancts tris(2-carboxyethyl)phosphine and dithiothreitol were used. Significant differences were observed for native and denatured RTX oxidation due to morphological changes and unfolding of the RTX native structure. Native R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…More than 30 years ago, oxidation (Y,W) signals were successfully applied for detection of different proteins [15,26,30,48]. Recently, changes in their structure such as denaturation, aggregation, phosphorylation have been studied using (Y,W) oxidation at carbon electrodes [12,15,[22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 30 years ago, oxidation (Y,W) signals were successfully applied for detection of different proteins [15,26,30,48]. Recently, changes in their structure such as denaturation, aggregation, phosphorylation have been studied using (Y,W) oxidation at carbon electrodes [12,15,[22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies of different proteins were in agreement with this work. Recently, oxidation of Met [22,33] and His [21,22] residues in proteins at carbon electrodes was reported but unambiguous experimental evidence of the origin of this oxidation is still needed. Very recently, His oxidation peak was not observed in His-containing angiotensin peptides at a basal plane pyrolytic graphite [32].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As denaturing agent, urea affects the secondary and tertiary structure without affecting the primary structure, the surfactant SDS dissolves hydrophobic proteins, and the reducing agent DTT disrupts disulphide bonds, which are essential for qualitative and quantitative analysis in proteomic mechanism investigation . Urea and SDS are not electroactive, unlike DTT, which is electroactive .…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade electrochemical methods have been one of the significant techniques in the expansion of sensors and biosensors due to its advantages of inexpensive, simplicity, quick response, nondestructive detection and convenient for in‐situ detection. But it was found that due to the inflexibility of the RTX 3D structure, the electron transfers between the electroactive amino acids in the internal of the RTX 3D structure and the surface of electrode is more difficult and no electrical signal could appear from the interaction of the RTX on the electrode surface . So, in order to obtain an appropriate analytical signal for quantitative determination of RTX, we used the DNA biosensor.…”
Section: Introductionmentioning
confidence: 85%